Jawi generator software - Noor Shalasiah Osman (Universiti Malaysia Perlis, 2008)
Nowadays, Jawi knowledge is becoming important not just to adult but also to growing also to growing children. This is because Jawi is thought in the Malaysian primary school syllabus. Therefore, there is a niche for growing or young children to learn Jawi at the initial stage of their life. Thus project basically is to develop a Jawi Generator Software that will generate and create Jawi script easily. It basically should flexible and sophisticated application for the use by either the jawi books author or the students that studied jawi. The main technology that should be used to develop this application is Java using Command Prompt to compile the source code. The system should has an interface that looks like an implementation of advanced calculator interface which is for displayed the jawi script and automatically combine it together to perform the word in Jawi.